“Discourses of Displacement” in the Ethnography of Léon-Gontran Damas and Poetry of Charles Baudelaire - Reyes Salas, Michael (Dalhousie French Studies, 2020)
It is not far-fetched to imagine that the French underclass that occupied the city streets Charles Baudelaire roamed as a flâneur could have turned up in the bagne, or penal colony, described by the Negritude poet Léon Damas in his ethnographic field work in Guyane. Through a literary analysis of Damas’ ethnography, Retour de Guyane (1938), in tandem with a selection of prose-poems by Baudelaire from Le Spleen de Paris (1869) and Les Fleurs du mal (1857), this article calls attention to the parallels between the observational methods of urban spectatorship they use to collect case studies for their writing. The interpretive approach I use acknowledges the crossover between literary creativity and sociological analysis and is informed by a theoretical framework that couples Negritude’s anticolonialism with carceral studies. My analysis of these texts is situated in the context of the French Third Republic’s laws against recidivism and vagrancy in the late nineteenth century, which carried the penalty of forced deportation to distant penal colonies, a punitive practice that continued into the early twentieth century. In Baudelaire’s case, changing sociopolitical circumstances in light of Hausmannisation necessitated new modes of how writers dealt with the capital city’s exclusionary development. In the case of Damas, his critique of mise en valeur culture and exploitative colonial scholarship prompted his departure from the conventional practice of salvage ethnography that feigned inclusive objectivity. The article focuses on passages that highlight overlapping colonial and carceral attributes within both the colony and metropole. In conclusion, I argue that Damas’ condemnation of the mission civilisatrice, alongside Baudelaire’s contestation of degraded urban environments, point towards a poetics of colonial society’s intoxication with power.